Features measurement analysis of pull-in voltage for embedded MEMS - Hajar Baghdadi; Mohamed Lamhamdi; Karim Rhofir (Institute of Advanced Engineering and Science, 2022)
The embedded micro electro mechanical systems (MEMS) is a technology that is creating a new era in all fields and especially in the internet of things (IoT) field. MEMS are necessary components for the realization of tiny micro/nano circuits. For this reason, designers are facing many challenges in designing embedded MEMS for achieving efficient products. The pull-in voltage is one of the most important parameters of MEMS design. In this work, we are interested in the analysis of some geometrical and mechanical parameters for the pull-in. The objective is to study of the concept of pull-in voltage in order to reduce it. First, we made a simulation to choose the appropriate material achieving a lower pull-in voltage. Then, we analysed the impact of geometrical parameters on the pull-in voltage. In this work, Finite element method using COMSOL Multiphysics® software is employed to compute the Pull-in voltage and study the behaviour of the MEMS Switch in order to optimize it. Pull-in voltage can be reduced by careful selection of the cantilever material and it can be further reduced by changing the beam parameters.